2018
DOI: 10.1111/and.13003
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in sperm functional competence through modified low‐dose packaging in French mini straws of bull semen

Abstract: To achieve the targeted artificial insemination coverage with the current rate of semen production, without affecting the conception rate, it needs to reduce the number of spermatozoa per insemination dose in India as per international practice. Therefore, this study was planned to perform different levels of semen dilution, compare in vitro post-thaw semen quality and develop a modified low-dose semen packaging method in French mini straw to minimise semen dilution effect. Sixteen ejaculates were collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 37 publications
2
27
0
Order By: Relevance
“…This was supported by other findings, which revealed that higher dilutions of semen had negative effect on capacitation and acrosome status of spermatozoa (Prathalingam, Holt, Revell, Jones, & Watson, 2006;Schembri, Major, Suttie, Maxwell, & Evans, 2002). Previous study had revealed that during cryopreservation, the proportion of acrosome intact sperm decreased by about 31%, and the proportion of noncapacitated spermatozoa reduced by about 27%, when semen of crossbred bulls was diluted from 20 million to 5 million spermatozoa (Karan et al, 2018). The reduced percentage of capacitated spermatozoa in anandamide-treated semen might be due to anandamides decapacitating nature (Kumar et al, 2018;Schuel et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…This was supported by other findings, which revealed that higher dilutions of semen had negative effect on capacitation and acrosome status of spermatozoa (Prathalingam, Holt, Revell, Jones, & Watson, 2006;Schembri, Major, Suttie, Maxwell, & Evans, 2002). Previous study had revealed that during cryopreservation, the proportion of acrosome intact sperm decreased by about 31%, and the proportion of noncapacitated spermatozoa reduced by about 27%, when semen of crossbred bulls was diluted from 20 million to 5 million spermatozoa (Karan et al, 2018). The reduced percentage of capacitated spermatozoa in anandamide-treated semen might be due to anandamides decapacitating nature (Kumar et al, 2018;Schuel et al, 2002).…”
Section: Discussionsupporting
confidence: 81%
“…We observed dilution drastically reduced post-thaw sperm quality in terms of reduced proportion of motile spermatozoa, live spermatozoa and increased proportions of dead spermatozoa, acrosome-reacted spermatozoa and capacitated spermatozoa particularly below 10 million spermatozoa in Sahiwal bulls. These reductions in these sperm quality parameters were in line with Karan et al (2018), who observed higher semen dilutions reduced (p < .05)…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations